Sedimentary Characteristics and Models of Restricted Braided River Deltas Under the Control of Paleogeomorphology: A Case Study of the Jingjingzigou Formation in the Ji 451 Well Area, Jimusar Sag - Zhang, Ruixin; Zhao, Xiaodong (International Journal of Natural Resources and Environmental Studies, 2026)
In order to clarify the sedimentary characteristics of restricted braided river deltas under the control of paleogeomorphology in the Jingjingzigou Formation of the Ji 451 well area in the Jimusar Sag, establish sedimentary models, and understand the distribution patterns of sedimentary sand bodies. A variety of methods, including paleogeomorphologic restoration, logging facies description, lithofacies and sedimentary facies classification, were comprehensively employed to conduct the research. The research indicates that (1) The study area features a paleogeomorphic pattern of "southern bulge and northern depression," with the Jinan uplift developing in the south and a paleolake in the north, separated by a slope formed by the movement of the two fault blocks of the Jinan Fault in the middle. (2) In the second member of the Jingjingzigou Formation in the study area, channel deposits are predominantly developed. Based on lithological characteristics and single-well sedimentary facies analysis, they can be classified into underwater distributary channel and inter-distributary bay microfacies. The underwater distributary channels are distributed in large sets, with interbedded deposits of inter-distributary bays and underwater distributary channels. (3) After being denuded, the clastic materials from the Jinan uplift were transported northward along the slope to the lake basin. With a slope developed in the northern part of the lake basin, the sediments carved out multiple braided channels there. During the transportation process, as the northern shore of the lake basin features a sloped terrain, the sediments are unable to overcome their own gravitational force to continue being transported forward. Ultimately, they accumulate within the lake basin, forming sedimentary bodies that are spatially restricted by the lake basin, with a limited distribution range. These sedimentary bodies differ from the braided river deltas in the traditional sense. In the study area, it is manifested by relatively steep slopes both onshore and underwater, with the lake shore being in close proximity to the foothills. The river channels are short, and they develop only up to the braided river stage before entering the lake water restricted by the local deep-depression paleotopography, forming sedimentary bodies. This sedimentary body features thick sand bodies that rapidly thin out and pinch out in the direction away from the provenance. The sediment sorting and rounding are relatively poor, yet it can serve as a reservoir. The research findings provide a basis for oil and gas exploration in the Ji 451 well area, while also enriching the sedimentary theory of braided river deltas.